Patient reported outcomes for quality of life (QOL) by Expanded Prostate Cancer Index (EPIC) on average 15 years post treatment. (September 2022) - Seymour, Zachary A.; Daignault-Newton, Stephanie; McLaughlin, P.W.; Sandler, Howard; Jackson, William; Johnson, Skyler B.; Miller, David; Wei, John; Sanda, Martin; Hamstra, Daniel A.
Highlights: Reported here are patient reported outcomes to 15.8 median years of follow up for initial therapy including brachytherapy, external beam radiotherapy, and radical prostatectomy. Differences within each domain across modalities differences were generally preserved beyond 6 years of follow up. Limited changes in quality of life over time suggest that shorter interval changes are largely representative of persistent changes in quality of life. Costly and time consuming reporting of long term quality of life beyond 2–5 years may be limited value in future studies. Abstract: Objective/purpose: Previously patient reported quality of life (QOL) was reported in men with prostate cancer a mean 2 and 6 years post treatment with open radical prostatectomy (RP), 3D conformal radiation therapy (3D CRT), or 125 I low dose rate (LDR) brachytherapy (BT). Herein we update the results 15 years post-treatment QOL. Materials/methods: The Expanded Prostate Cancer Index (EPIC) domains were scored with differences evaluated at a median 15.8 years follow up based upon mean EPIC summary domains by ANOVA with pairwise post-hoc comparisons adjusted for age. Patient differences of current survey from first cross-section are reported as median change in summary score for each treatment group at median of 2.2 and 6.0, and 15.8 years. Results: Among men still alive response rate was 52% in BT, 60% in 3D CRT, and 62% in RP resulting in 30, 41, and 330 QOL questionnaires to evaluate for each corresponding modality at median follow up of 15.8 years. Men were a mean 75.3, 83.6, and 79.3 years of age after RP, 3DCRT, and BT, respectively. At a median of 15.8 years, there were largely persistent differences in EPIC domains without substantial evolution in QoL from middle time points. Persistent worsening in urinary irritative and bowel domain with 3DRT or BT compared to RP. Trend towards worse urinary incontinence with RP were noted without statistical differences within radiotherapy options. Conclusion: As the EPIC patient reported outcomes with the longest follow-up, these data uniquely reveal temporal trends from 2 to 15 years post treatment. However, the treatment modalities of open RP, 3D CRT without image guidance or intensity modulation, and BT without peripheral loading or MRI guidance may not reflect modern techniques.